Detection Of The Thermal Front Using The Cayula-Cornillon Alghorithm: A Case Study Of The State Fisheries Management Area 713, Indonesia - Muhammad Yusuf; Maddatuang Maddatuang; Abdul Malik; Irwansyah Sukri; Andi Andariana (Universitas Negeri Medan, 2024)
Thermal fronts are pivotal in shaping the marine ecosystem, influencing the presence and distribution of marine species. This study delves into the fluctuating patterns of thermal fronts in Indonesian waters, specifically focusing on the State Fisheries Management Area of the Republic of Indonesia, known as WPPNRI, 713. We identified the distribution and frequency of thermal fronts across different monsoon seasons. Utilizing the extended Cayula Cornillon Algorithm – Single Image Edge Detection (CCA-SIED), we deploy a precise methodology for detecting these fronts, relying on sea surface temperature (SST) gradients to identify specific periods and regions. Our analysis encompasses extensive satellite data collected from Moderate Resolution Imaging Spectroradiometer (MODIS) level 3. Our findings unveil distinct seasonal variations, with a decrease in thermal fronts during the west monsoon and a surge during the east monsoon. Moreover, we identify regional disparities, with denser thermal fronts observed in the southern and middle regions compared to the northern areas. Furthermore, our study underscores the critical need to integrate oceanographic data with fisheries management strategies to address the impacts of climate variability on marine resources. The observed relationships between thermal fronts, nutrient distribution, and fish migration emphasize the necessity for ongoing, localized monitoring to develop adaptive management solutions. This research marks a significant step in characterizing thermal fronts in WPPNRI 713, laying the groundwork for future investigations into other ecologically significant fronts, including those related to chlorophyll, salinity, and nutrients, thereby enhancing our understanding of marine ecosystem dynamics.Keywords: Cayula Cornillon; Fishing Zone; Marine Ecosystem; Sea Surface Temperature; Thermal Fronts